Insights into the salt levels in bread offers in Slovenia: trends and differences - Kugler, Saša; Hristov, Hristo; Blaznik, Urška; Hribar, Maša; Hafner, Edvina; Kušar, Anita; Pravst, Igor (Frontiers in Nutrition, 2025)
Objective: Bakery products are considered as one of main dietary sources of sodium/salt in Slovenia. Our main objective was to assess the salt content in bread in Slovenia, focusing into different bread categories and sales channels. The data collected in 2022 was compared with year 2012.A follow-up study on salt content of bread sold in Slovenia was conducted. Bread samples were purchased in large retail shops and smaller bakeries across 11 statistical regions of Slovenia. Sodium content was determined by inductively coupled plasma mass spectrometry; salt content was calculated by multiplying sodium content with 2.54, assuming all sodium corresponds to sodium chloride.In 2022, 178 bread samples were purchased and analysed. Weighted mean salt content in bread was 1.35 (95% CI 1.28-1.42) g/100 g in 2012, and 1.26 (95% CI 1.22-1.29) g/100 g in 2022, showing a 7% decrease. Notable differences in the salt content were observed between various bread subcategories and retail environments. In addition, a significant difference was observed between white wheat bread sold in large retail shops and smaller bakeries, where a higher salt content was observed.While study results show small decrease in the salt content in bread in Slovenia in last decade, the salt reduction targets set by the WHO have not been met. Additional efforts are needed to stimulate bread reformulation with reducing salt content.